Fatigue and physical activity in cancer survivors: A cross‐sectional population‐based study. (12th March 2019) - Matias, Margarida; Baciarello, Giulia; Neji, Mohamed; Di Meglio, Antonio; Michiels, Stefan; Partridge, Ann H.; Bendiane, Marc Karim; Fizazi, Karim; Ducreux, Michel; Andre, Fabrice; Vaz‐Luis, Ines
Abstract: Purpose: A substantial proportion of cancer survivors experience fatigue after diagnosis. Physical activity (PA) can impact fatigue after cancer. In this study, we evaluated the prevalence and association of fatigue and the practice of PA in a population with early cancer. Methods: Using the national population‐based French cross‐sectional study Vie après le cancer 2, we included 1984 patients with early breast (61.1%), prostate (21.5%), and colorectal (17.4%) cancer. Severe fatigue at 2 years postdiagnosis was defined by a score ≥40 in the European Organization for Research and Treatment of Cancer quality of life questionnaire (EORTC QLQ C30) fatigue subscale. PA was defined as (a) self‐reported PA before diagnosis (active/inactive) and (b) change in PA since diagnosis (increased/maintained exposure vs decreased exposure/remaining inactive). Multivariate regression examined associations of severe fatigue with PA, adjusting for baseline clinical and treatment variables. Results: Median age was 52 years. 51.5% of patients experienced severe fatigue 2 years post‐diagnosis. 87.7% reported to be physically active before cancer diagnosis; 53.3% of patients either decreased PA or remained inactive at 2 years postdiagnosis. At 2 years postdiagnosis, severe fatigue was associated with a change in PA since diagnosis: patients with decreasing PA/remaining inactive from pre‐ to postdiagnosis had a higher risk of severe fatigue vs those with increasing/maintaining PA (adjusted odds ratio [95% confidence interval] 2.32 [1.85‐2.90]). Conclusion: Fatigue continues to be a substantial problem for cancer survivors 2 years after cancer diagnosis and is associated with PA decreasing/remaining inactive since diagnosis. Interventions to maintain or increase PA for cancer survivors should be tested to mitigate long‐term fatigue after cancer. Abstract : Fatigue continues to be a substantial problem for cancer survivors 2 years after cancer diagnosis and is associated with PA decreasing /remaining inactive since diagnosis. Interventions to maintain or increase PA for cancer survivors should be tested to mitigate long‐term fatigue after cancer.